C-POS: A Context-Aware Adaptive Part-of-Speech Language Learning Framework - Shazia Maqsood; Abdul Shahid; Fakhra Nazar; Muhammad Asif; Muhammad Ahmad; Manuel Mazzara (IEEE Access)
In the current age of technology, comprehension of the English language is very important. This is because that often innovation and discoveries are done by English speaking countries. And thus, it is considered as being the most important and widely used international language. Further, the need for learning an additional language has increased due to globalization in an unprecedented manner. Therefore, English is being taught as an additional language at various levels of education. In traditional classrooms of non-English speaking countries, students only learn English in their language classes whereas they have few opportunities to practice English outside the classroom. However, the specialized nature of mobile technologies has opened a new horizon for learners that make information available to people at any time, at any place, and in any form.The number of smartphone users is increasing every year and more than 4.78 billion smartphone users are in the world today.It can be understood that learning increases when the learning process is integrated with daily life routine activities. The context-awareness is one of the commonly used techniques that provide specialized content to different learners based on their context parameters. The word ’context’ refers to any information that can be used to characterize the situation of a particular entity. The context parameter includes location, time, concentration level, Interest and learner’s knowledge. Based on these context parameters, a Context-aware Part-Of-Speech (C-POS) learning system is designed, implemented and evaluated. Different experiments are conducted to evaluate the performance of learners’ which is increased by 9%. The evaluation of results provides evidence that the C-POS learning system can be successfully adapted by the non-natives speakers to learn the English language effectively.